Synthesis, characterization, and solar cell and transistor applications of phenanthro[1, 2‐b:8, 7‐b′]dithiophene–Diketopyrrolopyrrole semiconducting polymers. Issue 5 (6th January 2015) - Mori, Hiroki; Suetsugu, Masato; Nishinaga, Shuhei; Chang, Ning‐hui; Nonobe, Hikaru; Okuda, Yasuhiro; Nishihara, Yasushi
ABSTRACT Synthesis, characterization, and polymer solar cell and transistor application of a series of phenanthro[1, 2‐b:8, 7‐b′]dithiophene‐based donor–acceptor (D–A)‐type semiconducting polymers combined with a diketopyrrolopyrrole unit are reported. The present polymers showed some unique features such as strong aggregation behavior, high thermal stability, and short π–π stacking distance (3.5–3.6 Å), which are suitable for high performance organic materials. In addition, they have a significantly extended absorption up to 1000 nm with a band gap of ca. 1.2 eV. However, such strong intermolecular interaction reduced their solubility and molecular weights, which resulted in low crystalline nature and moderate field‐effect mobility of 0.01 cm2 V−1 s−1. Furthermore, such strong aggregation behavior led to the large‐scale phase separation in the blend films, which may prevent the effective photocurrent generation, limiting Jsc and power conversion efficiency of 2.0%. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 709–718